Kinematics and Subpopulations' Structure Definition of Blue Fox (Alopex lagopus) Sperm Motility using the ISAS® V1 CASA System. Issue 4 (2nd June 2014) - Soler, C; García, A; Contell, J; Segervall, J; Sancho, M
Contents: Over recent years, technological advances have brought innovation in assisted reproduction to the agriculture. Fox species are of great economical interest in some countries, but their semen characteristics have not been studied enough. To advance the knowledge of function of fox spermatozoa, five samples were obtained by masturbation, in the breeding season. Kinetic analysis was performed using ISAS ® v1 system. Usual kinematic parameters (VCL, VSL, VAP, LIN, STR, WOB, ALH and BCF) were considered. To establish the standardization for the analysis of samples, the minimum number of cells to analyse and the minimum number of fields to capture were defined. In the second step, the presence of subpopulations in blue fox semen was analysed. The minimum number of cells to test was 30, because kinematic parameters remained constant along the groups of analysis. Also, the effectiveness of ISAS ® D4C20 counting chamber was studied, showing that the first five squares presented equivalent results, while in the squares six and seven, the kinematic parameters showed a reduction in all of them, but not in the concentration or motility percentage. Kinematic variables were grouped into two principal components (PC). A linear movement characterized PC1, while PC2 showed an oscillatory movement. Three subpopulations were found, varying in structure among different animals.